Where Spirit and Bulldozer Roam: Environment and Anxiety in Highland Borneo - Amster, Matthew (Journal for the Study of Religion, Nature and Culture, 2008)
This paper explores changing perceptions of the natural environment among the Kelabit, an indigenous people of the Borneo interior. It considers both traditional and post-Christian conversion understandings about forest spaces. The former animistic ritual practices of the Kelabit centered on a spiritual dialogue with the natural world and this dialogue was often marked by active efforts to avoid or mitigate danger through ritual practice. One key example presented here is the former ceremony of ‘calling the eagle’ (nawar keniu), a ritual employed in times of crisis that exemplifies the dialogical and entwined relationship Kelabit had to the natural world. Such former animistic beliefs are contrasted with contemporary Christian practices, including a local mountain retreat on Mount Murud and present-day political and economic anxieties over logging in the Kelabit Highlands, as a means to consider relationships between religion and attitudes toward the environment among the Kelabit.